2004
DOI: 10.1002/ardp.200300757
|View full text |Cite
|
Sign up to set email alerts
|

Structure/Activity Investigations of 5‐Substituted 3‐Methylisoxazole[5, 4‐d]1, 2, 3‐triazin‐4‐one Derivatives

Abstract: The series of 5-substituted 3-methylisoxazole[5, 4-d]1, 2, 3-triazin-4-one derivatives was obtained by diazotization of 5-amino-3-methylisoxazol-4-carboxylic acid hydrazide. The immunological activity of these compounds was investigated experimentally in several in vitro and in vivo assays in mice and human models. In the next step, quantum-chemical investigations were performed using density functional theory with the B3LYP hybrid exchange-correlation energy functional and 6-31G(d, p) basis set. The Polarizab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…1,2,4-Triazines are a well-known class of heterocyclic compounds and display significant biological activity especially with condensed heterocyclic systems. Pyrimidine nucleic bases containing triazines show interesting properties; for example, azacytidine, a synthetic triazine analogue of cytidine, shows strong antileukemic activity. , PS-15, a prodrug of diaminotriazine, is active against resistant malarial strains . Moreover, triazine derivatives are cytotoxic to parasites since they offer excellent selectivity between parasites and host cells. A series of triazine derivatives was reported by Singh et al by the synthetic route shown in Scheme .…”
Section: Synthetic Antiamoebic Compoundsmentioning
confidence: 99%
“…1,2,4-Triazines are a well-known class of heterocyclic compounds and display significant biological activity especially with condensed heterocyclic systems. Pyrimidine nucleic bases containing triazines show interesting properties; for example, azacytidine, a synthetic triazine analogue of cytidine, shows strong antileukemic activity. , PS-15, a prodrug of diaminotriazine, is active against resistant malarial strains . Moreover, triazine derivatives are cytotoxic to parasites since they offer excellent selectivity between parasites and host cells. A series of triazine derivatives was reported by Singh et al by the synthetic route shown in Scheme .…”
Section: Synthetic Antiamoebic Compoundsmentioning
confidence: 99%
“…The structure/activity investigations were extended by the application of the B3LYP hybrid exchange-correlation energy functional and the 6-31G(d, p) basis set. [ 46 ] The Polarizable Continuum (SCRF/PCM) solvent model was also taken into account, in order to show the solvent influence on the electron density, and the electrostatic potential around the exemplary molecules. Correlations between the molecular structure and its biological properties were subsequently found by using a stepwise selection of scales for the multiple linear regression (MLR).…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, based on quantum chemistry calculation level of density function theory (DFT) [19,20], Berny energetic gradient and generalized gradient approximation (GGA) were employed to optimize the spatial conformation of coded amino acids. Then, the descriptor calculation web of molecular descriptor lab (MODEL) [21] …”
Section: Principle and Methodologymentioning
confidence: 99%